Characterization of MCM-41 Mesoporous Silica using the Hydrothermal Method - Indriani, Iin; Gusti, Herdie Idriawien; Agustina, Ayu Safitri; Karneng, Syahdam (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2024)
This research was conducted to determine the characteristics of MCM-41 mesoporous silica. The mesoporous silica synthesis process used the hydrothermal method. The main ingredients used were cetyltrimethyl ammonium chloride (STAK) surfactant as a structure directing agent and ludox HS-40 as a silica source. The synthesized MCM-41 mesoporous silica was then characterized by using X-Ray Powder Diffraction (XRD) and Fourier Transform Infrared (FTIR). The XRD characterization results showed several peaks indexed with decreasing intensity, namely (100), (110) (200) and (210). This is a typical peak possessed by MCM-41 mesoporous silica. These peaks followed a hexagonal structure pattern. The FTIR spectrum showed several distinctive peaks belonging to MCM-41 mesoporous silica.